Age- and Experience-Related Plasticity of ATP-Mediated Signaling in the Neocortex - Lalo, Ulyana; Bogdanov, Alexander; Pankratov, Yuriy (Frontiers in Cellular Neuroscience, 2019)
There is growing recognition of the important role of interaction between neurons and glial cells for brain longevity. The extracellular ATP have been shown to bring significant contribution into bi-directional glia-neuron communications, in particular into astrocyte-driven modulation of synaptic plasticity. To elucidate a putative impact of brain aging on neuron-glia networks, we explored the ageing-related plasticity of the purinoreceptors-mediated signalling in cortical neurons and astrocytes. We investigated the age- and experience-related alterations in purinergic components of neuronal synaptic currents and astroglial calcium signalling in the layer2/3 of neocortex of mice exposed to the mild caloric restriction (CR) and environmental enrichment (EE) which included ad libitum physical exercise. We observed the considerable age-related decline in the neuronal P2X receptor-mediated miniature spontaneous currents which originated from the release of ATP from both synapses and astrocytes. We also found out that purinergic astrocytic Ca2+-signalling underwent the substantial age-related decline but EE and CR rescued astroglial signalling, in particular mediated by P2X1, P2X1/5 and P2Y1 receptors. Our data showed that age-related attenuation in the astroglial calcium signalling caused a substantial decrease in the exocytosis of ATP leading to impairment of astroglia-derived purinergic modulation of excitatory synaptic currents and GABAergic tonic inhibitory currents. On a contrary, exposure to EE and CR, which enhanced purinergic astrocytic calcium signalling, up-regulated the excitatory and down-regulated the inhibitory currents in neurons of old mice, thus counterbalancing the impact of ageing on synaptic signalling. Combined, our results strongly support the physiological importance of ATP-mediated signalling for glia-neuron interactions and brain function. Our data also show that P2 purinoreceptor-mediated communication between astrocytes and neurons in the neocortex undergoes remodelling during brain ageing and decrease in the ATP release may contribute to the age-related impairment of synaptic transmission.